2018
DOI: 10.1021/acs.iecr.8b00017
|View full text |Cite
|
Sign up to set email alerts
|

Rattle, Porous, and Dense Cores and Discontinuous Porous, Continuous Porous, and Dense Shells in Pt@Au Core–Shell Nanoparticles

Abstract: In this study, Pt@Au core–shell nanoparticles were simulated by a classical molecular dynamics method to investigate the influences of morphologies of the core and shell regions on structural stability and melting behavior of these nanoparticles. For this aim, the nanoclusters with the same shell and different cores including rattle-core, porous-core, and dense-core types were considered. Through investigation of the shell effect, nanoclusters with the same core and different shells including dense-shell, cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 99 publications
1
4
0
Order By: Relevance
“…It is observed that the void space is unstable in all nanoparticles and is filled by the collapse of atoms. This result was observed in our previous studies on yolk–shell and hollow nanoparticles. Our previous results indicated that the stability of yolk–shell nanoparticles is dependent on the ratio of external radius to the shell thickness ( r ext /shell–thickness). The large nanoparticles with the largest shell–thickness have the smallest r ext /shell–thickness ratio and consequently have the highest void stability .…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…It is observed that the void space is unstable in all nanoparticles and is filled by the collapse of atoms. This result was observed in our previous studies on yolk–shell and hollow nanoparticles. Our previous results indicated that the stability of yolk–shell nanoparticles is dependent on the ratio of external radius to the shell thickness ( r ext /shell–thickness). The large nanoparticles with the largest shell–thickness have the smallest r ext /shell–thickness ratio and consequently have the highest void stability .…”
Section: Resultssupporting
confidence: 80%
“…Our results showed that dense-core and dense-shell NPs have the highest thermal stability. Also, results showed that porous-core and discontinuous porous-shell have the lowest thermal stability . In another work, our results showed that various structural factors such as geometries of the shell and core, core size, shell thickness, and shell composition are effective ways of increasing the thermal and structural stability of the YSNPs …”
Section: Introductionmentioning
confidence: 55%
See 3 more Smart Citations